Florida-Friendly Landscaping™ Guidelines Community Associations Can Use to Select a Landscaper and Write an Effective Landscaping Contract - Annemarie Post; Fred Santana (EDIS)
Revised! ENH1080, a 16-page fact sheet by Annemarie Post and Fred Santana, provides an example of language that could be included in a landscape maintenance contract for existing or new community associations. Includes helpful resources. Published by the UF Department of Environmental Horticulture, December 2009.